2022
DOI: 10.1038/s41368-021-00151-3
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent compressive force induces cell cycling and reduces apoptosis in embryoid bodies of mouse induced pluripotent stem cells

Abstract: In vitro manipulation of induced pluripotent stem cells (iPSCs) by environmental factors is of great interest for three-dimensional (3D) tissue/organ induction. The effects of mechanical force depend on many factors, including force and cell type. However, information on such effects in iPSCs is lacking. The aim of this study was to identify a molecular mechanism in iPSCs responding to intermittent compressive force (ICF) by analyzing the global gene expression profile. Embryoid bodies of mouse iPSCs, attached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Mechanical stimulation has been reported to affect the growth and differentiation of stem cells. Our group previously demonstrated that intermittent compressive force promotes proliferation and suppresses apoptosis in RA-treated embryoid bodies of mouse iPSCs 21 . This implies a role for mechanical stimuli in promoting iPSC proliferation.…”
Section: Discussionmentioning
confidence: 95%
“…Mechanical stimulation has been reported to affect the growth and differentiation of stem cells. Our group previously demonstrated that intermittent compressive force promotes proliferation and suppresses apoptosis in RA-treated embryoid bodies of mouse iPSCs 21 . This implies a role for mechanical stimuli in promoting iPSC proliferation.…”
Section: Discussionmentioning
confidence: 95%
“…Mechanical stimulation has been reported to affect the growth and differentiation of stem cells. Our group previously demonstrated that intermittent compressive force promotes proliferation and suppresses apoptosis in RA-treated embryoid bodies of mouse iPSCs 18 . This implies a role for mechanical stimuli in promoting iPSC proliferation.…”
Section: Discussionmentioning
confidence: 95%
“…An intermittent compressive force (ICF) was applied for 24 h. A compressive force apparatus was used, as described previously (Manokawinchoke et al, 2015; Manokawinchoke, Limraksasin, et al, 2022). The compressive force was generated by applying load on the culture medium using a pestle moving up and down in a matched‐size well plate.…”
Section: Methodsmentioning
confidence: 99%